Explaining public stigma of grieving persons during COVID-19 - Zammit, Tamara (Curtin University, 2023)
This thesis investigates public stigma towards individuals bereaved by COVID-19 with PGD. Study 1 examines the differences in public stigma reported toward an individual bereaved by COVID-19 death with prolonged grief disorder (PGD). Study 2 examines the differences in public stigma reported toward an individual bereaved by COVID-19 death with an underlying medical condition with PGD. Both studies showed participants reported significantly more public stigma towards bereaved individuals with PGD than those without PGD.